2008
DOI: 10.1177/1753193408090757
|View full text |Cite
|
Sign up to set email alerts
|

A Finite-Element Analysis of Kienböck’s Disease

Abstract: A finite-element analysis model of the lunate was established using geometrical data obtained from cadaveric bones. The lunate cortex was modelled with triangular and quadrilateral elements and its intraosseous structure was represented either as a homogenous elastic structure or as an anisotropic network of cortical bone beams (trabeculae) with different orientations and thicknesses. Compressive loads applied to the metacarpus were distributed in the carpus against the fixed radius and ulna. The ulnar varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Simulation of several scaphoid bone fracture were performed, which could explain the clinical evolution of the behavior of the wrist. He also developed a more realistic threedimensional FE model of lunate bone to investigate the specific Kienbock's disease [14]. Carrigan et al [15] developed a FE model to study the load transmission into the carpus under static load and concluded to the importance of the cartilage and the rotational degree of freedom of the carpal in the pressure distribution into the wrist.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation of several scaphoid bone fracture were performed, which could explain the clinical evolution of the behavior of the wrist. He also developed a more realistic threedimensional FE model of lunate bone to investigate the specific Kienbock's disease [14]. Carrigan et al [15] developed a FE model to study the load transmission into the carpus under static load and concluded to the importance of the cartilage and the rotational degree of freedom of the carpal in the pressure distribution into the wrist.…”
Section: Introductionmentioning
confidence: 99%
“…Ledoux et al (11) proposed that ulnar minus, lunate uncovering, and angulated trabecular cause the micro fractures not to heal properly. Garcia-Elias and Vidal (13), in a group of KD 28 men and 12 women, connected the lunate length to lunate morphology but assumed some exceptions, unlike the Schuurman et al (14) with 68 wrists with no connection of ulnar length to lunate shape.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that the morphology and microstructure of the wrist bones, intraosseous pressure, and mechanical stresses have etiologic and prognostic values (3)(4)(5). Ulnar variance (UV) is a good example of many author's attempt to show that the negative UV is playing a key role (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), despite many normal individuals with a negative UV, that doesn't get KD (6) and many KD patients with positive UV (16). One of the theories that has repeatedly been proposed is the effect of lunate morphology in KD, either as an etiologic or a prognostic factor like Viegas and Zapico (15,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Lunatomalacia, one of the main causes of wrist pain, is a disease characterized by cystic change, fragmentation and progressive collapse of the lunate (13). Lunatomalacia was first reported by Peste in 1843.…”
Section: Introductionmentioning
confidence: 99%